Art of peripheral permeability: Revisiting interfaces in biological media for post-biological culture. Issue 2 (1st December 2012) - Ljubec, Živa
As the title of this article suggests, the concept of the interface needs to be revisited in the context of biological media in order to infer some implications for the post-biological culture. A direct comparison of our media culture to the environmental notion of the media and the natural partitioning of the media by biological membranes becomes possible if we expand on the notions of media and interfaces in our technologically conditioned realities. The question of periphery and permeability of a biological membrane will be addressed in the context of the theory of aesthetics. Although at first glance we are dealing only with subtle changes in the degree of permeability of an interface, suddenly selectiveness in permeability arises, and though an interface is considered simply peripheral, at a slight touch with an opposing media its role swiftly becomes central. Taking into account the functioning of a biological membrane, a remarkably resourceful technology, associations stem from the culture on the cellular level to the culture of human society, where the human being should not be limited to the concept of self, but operatively diffused into collective awareness. The technologies that we develop, and the media we employ and inhabit always meet at an interface. But there is more to the face-to-face meeting of media than a mere inert surface. Such a surface as a membrane is not abstractly thin but more like 'infrathin' – the term invented by the artist Marcel Duchamp. What happens at such confrontation of media of different kinds, of incomparable qualities, will be further discussed in the article. The dynamics of permeability at the periphery adjust the tension between heterogeneous qualities of the media to allow for coexistence, even for the emergence of new meanings. This heterogeneity can be experienced only within the interface, and therefore an inner view is proposed instead of a view from above, an inner view that prevents reduction of processes to commensurable, quantifiable objects. Since interface occurs at every interaction with the world, as explained in the theory of endophysics by biochemist Otto E. Rössler, we have to be aware of the problematics of this phenomenon, and we must rethink its potential. The interface is at the same time an opportunity, the interval we are given, where our drive to act is suppressed and our will to speculate prevails. By contemplating intricate biological solutions, this article hopes to further encourage the turn towards post-biological evolution of our awareness.